Oriental Medicine Samhwangsasim-tang Alleviates Experimental Autoimmune Encephalomyelitis by Suppressing Th1 Cell Responses and Upregulating Treg Cell Responses - Lee, Min J.; Choi, Jong H.; Lee, Sung J.; Cho, Ik-Hyun (Frontiers in Pharmacology, 2017)
Oriental medicine Samhwangsasim-tang (SHSST) has traditionally been used in East Asia to treat hypertension and its complications. However, little is known about its potential value regarding the treatment of chronic inflammatory diseases such as multiple sclerosis (MS). In this study, we investigated whether SHSST has a beneficial effect in treating myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis (EAE). Onset-treatment with SHSST was found to alleviate neurological symptoms as well as demyelination and glial activation in the spinal cords from the EAE mice. The SHSST also attenuated the mRNA or protein expression of pro-inflammatory cytokines (interleukin-1beta and tumor necrotic factor-alpha); chemokines (RANTES, monocyte chemotatic protein-1, and macrophage inflammatory protein-1alpha); inducible nitric oxide synthase; and cyclooxygenase-2 in correspondence with the down-regulation of the nuclear factor-kappa B and mitogen-activated protein kinases signal pathways in the spinal cords from EAE mice. Interestingly, the protective effect of the SHSST was related to a decreased number of Th1 cells and an increased number of Treg cells in spinal cords from EAE mice. Taken together, our finding firstly suggested that SHSST could delay or mitigate EAE with a wide therapeutic time-window by suppressing Th1 cell responses and upregulating Treg cell responses. Also, our findings are strong enough to warrant further investigation of SHSST as a treatment for chronic autoimmune diseases including MS.